Childhood Head and Neck Lymphadenopathy: A Report by a Single Institution (2003-2017). Issue 1 (January 2019) - Indolfi, Paolo; Perrotta, Silverio; Rossi, Francesca; Di Martino, Martina; Pota, Elvira; Di Pinto, Daniela; Gualdiero, Giovanna; Boccieri, Emilia; Indolfi, Cristiana; Casale, Fiorina
Abstract : Actually, there is still no consensus related to diagnostic and management algorithms in case of head and neck lymphadenopathy in children. The aim of our study was to analyze the causes of head and neck lymphadenopathy in children to determine a systematic diagnostic approach. We enrolled all cases of head and neck lymphadenopathy in children under the age of 18 diagnosed at the Unit of Hemato-Oncology, Pediatric Department of University "Luigi Vanvitelli, " Naples, over a 15-year period (January 2003-December 2017). In total, 405 patients (271 males) were enrolled in the study. Thirteen cases due to other causes, were left off the study. Therefore, the study was performed on 392 cases. A total of 220 patients (56.1%) had a history of infection, 66 cases (16.8%) a diagnosis of neoplasia, and 101 (24.9%) cases a diagnosis of reactive inflammatory changes of nonspecific origin. We have observed the following from our study: (1) the acute infections are the most common causes of head and neck lymphadenopathy in the pediatric population; (2) in about a quarter of patients, the lymphadenopathy resulted by nonspecific origin; (3) the supraclavicular nodes should be regarded with a high index of suspicion of malignancy.